The Earlier the Better? Individual Participant Data and Traditional Meta‐analysis of Age Effects of Parenting Interventions. Issue 1 (14th September 2018) - Gardner, Frances; Leijten, Patty; Melendez‐Torres, G.J.; Landau, Sabine; Harris, Victoria; Mann, Joanna; Beecham, Jennifer; Hutchings, Judy; Scott, Stephen
Abstract : Strong arguments have been made for early intervention for child problems, stating that early is more effective than later, as the brain is more malleable, and costs are lower. However, there is scant evidence from trials to support this hypothesis, which we therefore tested in two well‐powered, state‐of‐the‐art meta‐analyses with complementary strengths: (a) Individual participant data (IPD) meta‐analysis of European trials of Incredible Years parenting intervention ( k = 13, n = 1696; age = 2–11); (b) Larger, trial‐level robust variance estimation meta‐analysis of a wider range of parenting programs ( k = 156, n = 13, 378, M age = 2–10) for reducing disruptive behavior. Both analyses found no evidence that intervention earlier in childhood was more effective; programs targeted at a narrower age range were no more effective than general ones. Abstract : The title for this Special Section isMeta‐analysis and Individual Participant Data Synthesis in Child Development, edited by Glenn I. Roisman and Marinus H. van IJzendoorn